2013
DOI: 10.1001/jamapsychiatry.2013.268
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity of Patients With Schizophrenia, Autism, Bipolar Disorder, Depression, Anorexia Nervosa, or Substance Abuse vs Their Unaffected Siblings

Abstract: It is unknown how genetic variants conferring liability to psychiatric disorders survive in the population despite strong negative selection. However, this is key to understanding their etiology and designing studies to identify risk variants. Objectives: To examine the reproductive fitness of patients with schizophrenia and other psychiatric disorders vs their unaffected siblings and to evaluate the level of selection on causal genetic variants. Design: We measured the fecundity of patients with schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
252
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(280 citation statements)
references
References 60 publications
(62 reference statements)
20
252
4
4
Order By: Relevance
“…Because individuals with ASD have drastically reduced fecundity (11), the net prediction is that these target genes should be under severe purifying selection, and hence have a reduced load of disruptive variants in the human gene pool. Here, we validate this prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because individuals with ASD have drastically reduced fecundity (11), the net prediction is that these target genes should be under severe purifying selection, and hence have a reduced load of disruptive variants in the human gene pool. Here, we validate this prediction.…”
Section: Discussionmentioning
confidence: 99%
“…We computed that roughly half of the time in males, a DN LGD mutation within an autism gene will produce severe ASD (10). Because people with ASD have lower fecundity than the general population, a disruptive mutation in an autism gene will be under strong purifying selection and quickly eliminated from the population (11). A clear prediction is that autism genes will have a smaller load of disruptive mutations than "typical" genes, as we first observed for fragile X mental retardation protein (FMRP)-associated genes (5,12).…”
mentioning
confidence: 99%
“…Large-scale studies based on historical registries have indicated that patients with SCZ have strongly reduced fecundity [53][54][55], whereas their siblings may have increased or decreased reproductive success depending on gender [53,54]. The overall effect calculated for affected patients and their siblings indicated that these families contribute fewer descendants to the new generation compared with families with no members affected by SCZ [53,54]. Similar results have been reported for BPD, although the decrease in fecundity seems to be less marked than that observed for SCZ [53,55].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study used Swedish register data. The study reported no decrease in the number of children for women with life-time depression; small decreases in fecundity (fertility ratio between 0.70 and 0.95) in men with bipolar disorder, women with bipolar disorder, men with depression, women with anorexia nervosa, and men and women with substance abuse and a strong reduction of fecundity (FR between 0.2 and 0.5) in men and women with schizophrenia, men and women with autism and men with anorexia nervosa (Power et al, 2012).…”
Section: Fecundity and Mental Disordersmentioning
confidence: 99%